Hex-dominant meshing: Mind the gap!. (September 2018) - Ray, Nicolas; Sokolov, Dmitry; Reberol, Maxence; Ledoux, Franck; Lévy, Bruno
Abstract: We propose a robust pipeline that can generate hex-dominant meshes from any global parameterization of a tetrahedral mesh. We focus on robustness in order to be able to benchmark different parameterizations on a large database. Our main contribution is a new method that integrates the hexahedra (extracted from the parameterization) into the original object. The main difficulty is to produce the boundary of the result, composed of both faces of hexahedra and tetrahedra. Obviously, this surface must be a good approximation of the original object but, more importantly, it must be possible to remesh the volume bounded by this surface minus the extracted hexahedra (called void). We enforce these properties by carefully tracking and eliminating all possibilities of failure at each step of our pipeline. We tested our method on a large collection of objects (200+) with different settings. In most cases, we obtained results of very good quality as compared to the state-of-the-art solutions. To ease reproducing our results and benchmarks, we provide a C++ implementation of the pipeline in the supplemental materials. Graphical abstract: Highlights: We present a robust method of generating hex-dominant meshes free of degenerate or flipped elements. It allows to plug in specialized algorithms for meshing particular geometries, such as fillets or tubular structures. We publish an open source implementation.